Preferences and Attitudes Regarding Adjunct Breast Cancer Screening Among Patients with Dense Breasts. Issue 2 (28th February 2020) - Miller, Matthew M; Repich, Kathy; Patrie, James T; Anderson, Roger T; Harvey, Jennifer A
Abstract: Objective: New breast screening modalities are being investigated to address the need for more sensitive breast cancer screening in women with dense breasts. We investigated the preferences and attitudes of these patients regarding adjunct screening modalities to help evaluate the acceptability of these exams. Methods: In this institutional review board–approved prospective study, patients with dense breasts on their prior mammogram were invited to complete a survey. Patients were asked to estimate their personal breast cancer risk compared with peers, indicate their level of concern related to screening callbacks, radiation exposure, and intravenous (IV) contrast allergies, and identify which factors might deter them from getting adjunct screening exams. Results: Five hundred eight patients with dense breasts presenting for screening mammography completed surveys. While most patients (304/508, 59.9%) felt it was likely or very likely that cancer could be missed on their mammogram, only 8.9% (45/508) had undergone adjunct screening exams in the past 3 years. The most commonly cited deterrents to adjunct screening were cost (340/508, 66.9%), pain (173/508, 34.1%), and concern that adjunct screening could lead to additional procedures (158/508, 31.1%). When asked to select among three hypothetical breast cancer screening modalities, patients strongly preferred the more sensitive examination, even if this involved greater cost (162/508, 31.9%) or IV-contrast administration (315/508, 62.0%). Conclusion: Our data suggest that patients with dense breasts prefer adjunct screening exams that are both sensitive and inexpensive, although an increase in sensitivity could outweigh additional cost or even IV-line placement.